?DETtRMINATION OF THERMODYNAMIC PARAMETtRS FOR THE DECOMPOSITION OF SOME METAL CHELATES OF SUBSTITUTED HYDRAZOPYRAZOLONES - ALi , LAlLA I.; STEFAN , SHAKER L. (Biological Sciences - PJSIR, 2022)
The relative thermodynamic parameters of aseries of metal derivatives ofhydrazopyrazolone dyes containing meta -OH, -COOH, and -OCH3 groups have been determined by TGA, DTG and differential thermal analysis (DTA). The effects of substitutent on the hydrazo-rnoicty of the ligand on the stability of the complexes arc discussed. The affinity of different ligands for complexation with metal ions MO+[M=U022., Fe3., Cu2• and I-Ig’ 1reaches its highest value with metahydroxyphenylhydrazopyrazolone. The relative order of thermal stability is : UO/+ > Fe3+> Cu2+> Hg2+.The data were correlated and the results were used to explain the stabilization of such chclatcs by dative 1t-bonding between MDt and the ligand.